STUDIES ON THE INFLUENCE OF VARIOUS FACTORS ON LIPASE PRODUCTION USING PSEUDOMONAS CEPACIA - B.DHEVAHI; R.GURUSAMY (International Journal of Pharma and Bio Sciences, 2014)
Food Processing industry is always expecting economic and green technologies for the fat and oil modification. Microbial lipases are of immense importance and have gained special industrial attention in almost all industries . A new strain of lipolytic Pseudomonas cepacia was isolated from the oil industrial waste soil on a selective medium that contained olive oil as the only source of carbon and energy. The isolated strain was cultivated for lipase production in shake flasks at 30±10C and the effect of various fermentation conditions were studied. The maximum extracellular lipase activity of 15.15 U/ml and 15.30 U/ml were noticed for 30 g/l sucrose and 25 mg/l yeast extract respectively. The optimal cultural temperature was 400C and pH 6.0. Metal iron (Fe) also enhanced the lipase yield as supplementary.